2007
DOI: 10.1152/jn.00891.2006
|View full text |Cite
|
Sign up to set email alerts
|

Loading the Limb During Rhythmic Leg Movements Lengthens the Duration of Both Flexion and Extension in Human Infants

Abstract: Musselman KE, Yang JF. Loading the limb during rhythmic leg movements lengthens the duration of both flexion and extension in human infants. J Neurophysiol 97: 1247J Neurophysiol 97: -1257J Neurophysiol 97: , 2007. First published December 6, 2006; doi:10.1152/jn.00891.2006. Sensory input is critical for adapting motor outputs to meet environmental conditions. A ubiquitous force on all terrestrial animals is gravity. It is possible that when performing rhythmic movements, animals respond to loadrelated feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 59 publications
3
27
2
Order By: Relevance
“…However, when the hindlimbs were loaded, r EXT increased considerably while r FLEX went toward 0. Similar results were found in human infants when loading was applied to the legs in a variety of actual rhythmic movements (Musselman and Yang 2007). Thus stance-related inputs (i.e., force, stretch of ankle extensors, and/or pressure to the plantar surface) can considerably modify the regulation of phase durations and variations.…”
Section: Control Of Phase Durations and Phase Variations: Similar Consupporting
confidence: 73%
“…However, when the hindlimbs were loaded, r EXT increased considerably while r FLEX went toward 0. Similar results were found in human infants when loading was applied to the legs in a variety of actual rhythmic movements (Musselman and Yang 2007). Thus stance-related inputs (i.e., force, stretch of ankle extensors, and/or pressure to the plantar surface) can considerably modify the regulation of phase durations and variations.…”
Section: Control Of Phase Durations and Phase Variations: Similar Consupporting
confidence: 73%
“…6) were similar to those reported for walking in hatchlings, although modest positive correlations were reported for swimming and walking (Johnston and Bekoff 1996). TA burst duration does not typically follow changes in locomotor cycle duration (Grillner 1981) but can vary with cycle duration when a mechanical load is applied to ankle dorsiflexors during stepping (Musselman and Yang 2007). Thus TA burst frequency and duration during RLMs appeared to be controlled in a manner consistent with muscle activity controlled by a locomotor burst generator.…”
Section: Rlms Share the Frequency Range Of Fast Locomotor Burst Genersupporting
confidence: 71%
“…There are controversial data in the literature concerning the effect of foot loading on the cycle duration and walking speed. For instance, Stephens and Yang (1999) found that loading during the stance phase of walking in adults increases the extensor EMG amplitude but does not change the duration of the step cycle (see also Misiaszek, Stephens, Yang, and Pearson (2000)), while a large change in timing was seen in the infants (Musselman & Yang, 2007). Furthermore, the changes in duration of phases may be more prominent in reduced preparations than in intact animals (Duysens & Stein, 1978;Stephens & Yang, 1999;Whelan & Pearson, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ability of any single input to entrain or affect the locomotor rhythm is much reduced when competing with the input from other afferents and descending pathways (Ivanenko, Grasso, & Lacquaniti, 2000;Stephens & Yang, 1999;Whelan & Pearson, 1997). A current view on the role of different mechanoreceptors considers task-and context-dependent contribution of sensory inputs (Pearson, 2004), as well as its maturation in early development (Dominici, Ivanenko, & Lacquaniti, 2007;Musselman & Yang, 2007). In addition, the organization of the interneuronal network for locomotion and the use of corrective reactions during walking points toward a rule-based finite control system rather than a simple additive principle of multisensory fusion (Misiaszek, 2006;Prochazka, 1996).…”
Section: Introductionmentioning
confidence: 99%